2020
DOI: 10.1289/ehp5732
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth among Infants Exposed to in Utero Ultrafine Particles from Aircraft Emissions

Abstract: INTRODUCTION: Ambient air pollution is a known risk factor for adverse birth outcomes, but the role of ultrafine particles (UFPs) is not well understood. Aircraft-origin UFPs adversely affect air quality over large residential areas downwind of airports, but their reproductive health burden remains uninvestigated. OBJECTIVES: This analysis evaluated whether UFPs from jet aircraft emissions are associated with increased rates of preterm birth (PTB) among pregnant mothers living downwind of Los Angeles Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 74 publications
(81 reference statements)
0
25
0
Order By: Relevance
“…Emissions related to aircraft and airport have gained important attention in the last decades. A large number of studies have shown that emissions related to aircraft engine have significant impacts on air quality (Westerdahl et al , 2008; Masiol and Harrison, 2014; Shirmohammadi et al , 2017; Dinc, 2017), which affect adversely general public health and especially residential populations the vicinity airports (Barrett et al , 2010; Stettler et al , 2011; Habre et al , 2018; Wing et al , 2020; Song and Shon, 2012). Emissions related to aircraft are associated with a range of adverse health impacts including especially premature mortality, heart attacks, lung cancer, respiratory illness, and so on (Tokuslu, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emissions related to aircraft and airport have gained important attention in the last decades. A large number of studies have shown that emissions related to aircraft engine have significant impacts on air quality (Westerdahl et al , 2008; Masiol and Harrison, 2014; Shirmohammadi et al , 2017; Dinc, 2017), which affect adversely general public health and especially residential populations the vicinity airports (Barrett et al , 2010; Stettler et al , 2011; Habre et al , 2018; Wing et al , 2020; Song and Shon, 2012). Emissions related to aircraft are associated with a range of adverse health impacts including especially premature mortality, heart attacks, lung cancer, respiratory illness, and so on (Tokuslu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Emissions related to aircraft are associated with a range of adverse health impacts including especially premature mortality, heart attacks, lung cancer, respiratory illness, and so on (Tokuslu, 2020). Wing et al drew attention to premature birth among infants exposed to emission related to aircraft (Wing et al , 2020). Barrett et al (2010) pointed out that approximately 10,000 preterm fatalities per year could be attributed to aircraft operations at the LTO cycle (20 per cent) and non-LTO cycle (80 per cent) (Barrett et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential impacts of UFPs on sensitive populations, only the European Union regulates UFPs, albeit only filterable UFPs >23 nm from vehicles, (6) and there are no policies in occupational settings (7). While there is growing evidence from animal studies on the effects of in utero UFP exposure on development and subsequent disease (8), there have been relatively few studies in humans (9). Here, Wright and colleagues (10) add to this weight of evidence with the first analysis of prenatal UFP exposure and incident asthma in a prospective birth cohort in the United States (US).…”
mentioning
confidence: 99%
“…Thus, these may be relatively healthy cohorts and this bias may result in underestimating the effects of in utero UFP exposure in the general population. For example, children with the highest UFP prenatal exposures may have been more likely to be born before 37 weeks ( 9 ). Although the study adjusts for tobacco smoke exposure, future studies should account for e-cigarette exposures, which contain more nanosized particles and may confound the relationship with ambient UFPs ( 16 ).…”
mentioning
confidence: 99%
“…A recent study in Environmental Health Perspectives reports on the association between preterm birth and another source of air pollution—aircraft emissions. 4 …”
mentioning
confidence: 99%